Evaluation of Physicochemical Parameters of Lake Mechefera for Fish Culture, Ethiopia - Misebo, Tsegaye Dobamo; Wanore, Denebo Sebaro; Ayano, Wondimu Ersino; Gute, Rediet Markos; Badulo, Tesfaye Lamore (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Optimum fish production is dependent on the quality of the water. Hence, an investigation on standard water quality requirements for fish culture is very important. The present study was aimed at investigating the water quality of Lake Mechefera for suitability of fish culture in Misrak Badawacho district, Southern Ethiopia. For the laboratory investigation, samples of the water from Lake Mechefera were collected according to standard laboratory guideline for the analysis of water quality parameters. The following water quality parameters were measured in the laboratory and in the field: temperature (thermometer); pH (pH meter); electrical conductivity (conductivity meter); total dissolved solids (volumetric analysis); turbidity (Secchi disk), total hardness (titration method), dissolved oxygen (winkler method), and biological oxygen demand (BOD incubator model. The mean and standard deviation of the results obtained were: pH (8.59±0.01), electrical conductivity (6.23±0.08 μs/cm), temperature (21.43±1.20C), total dissolved solids (1162mg/l to 1329 mg/l), turbidity (3.26±0.15 NTU), total hardness (98.2±0.65 mg/l), dissolved oxygen (4.09±0.51) and biological oxygen demand (4.08±0.64). Generally, most of the water quality parameters evaluated in this study were within the range recommended for fish culture. The implications are that the water sampled in the Lake Mechefera is fit for fish culture with some modification of the water parameters. Further study is needed on phytoplankton diversity and the other remaing water paramers.